Desenvolvimento e implementação de uma micro-rede avançada de alta freqüência para integração de fontes alternativas de energia - Corrêa, Jeferson Marian (2006)
This Thesis presents a distributed generation system, which works as a Microgrid, suitable to integrate alternative energy sources, using a high frequency AC link (HFAC) as a means of connecting sources and loads. The static compensation of current harmonics, reactive power and voltage harmonics, which can be found in the Microgrid, is considered a key factor for the effective utilization of such distributed generation scheme. These multiple goals can simultaneously be achieved by using a Unified Power Quality Conditioner (UPQC). The UPQC controller is designed based on the instantaneous power theory (or p-q theory), which is used to obtain the power components to be compensated and, lately, the instantaneous current and voltage references for static compensation. Electronic power converters are used as the active elements, supplying the compensating current and voltage, in order to optimize the usage of the available energy resources. Additionally, this project aims to incentive the utilization of alternative energy sources, such as fuel cell stacks and solar panels, as the main elements in a distributed generation approach. Besides that, the utilization of a high frequency Microgrid, allows the instantaneous bi-directional power conversion, without the need of using bulky energy storage elements. As a main goal, this project proposes a platform for energy generation, operating as a Microgrid, with full static compensation capability and with the possibility to inject energy into the mains grid.